Does Exercise Testing Affect the Bioelectrical Impedance Assessment of Body Composition in Children? - Goss, F. L.; Robertson, R. J.; Dube, J.; Lenz, B.; Ranalli, J.; Frazee, K. (Pediatric Exercise Science, 2003)
This investigation examined the impact of a cycle ergometry exercise test (CET) on body composition determined using leg-to-leg bioelectrical impedance analysis (BIA; Tanita Model TPF-305). Fifty three children (25 males, 28 females) aged 10-12 yr participated. BIA measures of body fat (BF) were obtained immediately before and within five min of a multistage CET administered to assess peak oxygen consumption. Correlations (P = 0.01) of 0.99 were noted between the pre and post CET measures of BF. A systematic difference was not found in BIA measures obtained before and after CET. BF decreased by 0.4 and 1.2% following CET in the male and female subjects, respectively.